EXTH-57. PLASMA AND CEREBROSPINAL FLUID PHARMACOKINETICS OF THE PROCASPASE-ACTIVATING COMPOUND, PAC-1, FOLLOWING ORAL ADMINISTRATION IN A NON-HUMAN PRIMATE MODEL. (5th November 2018) - McCully, Cynthia Lester; Cruz, Rafael; Lyubimov, Alexander V; Zakharov, Alexander D; Fischer, James H; Hergenrother, Paul J; Warren, Katherine E
Abstract: BACKGROUND: PAC-1 is a novel compound which induces apoptosis via activation of the procaspase-3 pathway in cancer cells. Human clinical trials are ongoing with PAC-1 as a single agent (late-stage cancers) and in combination therapies (malignant glioma), in addition to studies in pet canines (glioma). This study evaluated the CSF penetration of PAC-1 via plasma and CSF pharmacokinetics in a nonhuman primate CSF Ventricular Reservoir or Lumbar Port model that allows serial CSF collection. METHODS: 4 male rhesus macaques received 15 mg/kg (Human Equivalent Dose of 558 mg/m 2 /day) of PAC-1 in 6 studies with two formulations; liquid (n=1) or pill (n=5). 1 animal received both formulations. Paired plasma and CSF (lumbar n=2 and ventricular n=4) samples were collected for 0–72 hours. PAC-1 was quantified by LC-MC/MS. The lower limit of quantitation for plasma was 10.0 ng/ml and CSF 0.2 ng/ml. PK parameters were calculated via noncompartmental methods. RESULTS: 5 studies were evaluable (n=1 liquid and n=4 pill). Plasma-Quanitifible (n=5). Liquid Formulation (n=1): AUC0-∞ 5299.91 hr*ng/ml, Half-Life 4.99 hr, and Clearance 57.43 L/hr/m 2 . Pill Formulation PK range (n=4): AUC0-∞ 1527.7–8036.08 hr*ng/ml, Half-Life 10.2–31.5 hr, and Clearance 37.65–199.49 L/hr/m 2 . CSF-Quanitifible (n=3; 2 lumbar & 1 ventricular) or undectable (n=2 ventricular). Liquid Formulation (lumbar n=1): AUC0-∞ 50.90 hr*ng/ml, Half-Life 4.59 hr, and Clearance 5979.56 L/hr/m 2 Pill Formulation PK range (lumbar n=1 and ventricular n=1): AUC0-∞ 7.53–31.25 hr*ng/ml, Half-Life 22.35–28.88 hr, and Clearance 9955.96–40178.44 L/hr/m 2 . CSF: Plasma Ratio formulation comparison: 0.96% liquid and 0.46% pill. CONCLUSIONS: In this animal model, the CSF penetration of PAC-1 is low and formulation-dependent, with CSF: Plasma ratio 2 fold greater with liquid verses pill formulation. The CSF clearance is rapid. FUTURE STUDIES: 10.08 and 12.1 mg/kg dosages (Human Equivalent Dose 375 and 450, mg/m 2 /day, respectively) are currently undergoing evaluation in this NHP model.